"Henry V": A Report on the Condition of the World - Gibińska, Marta (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
The central interest of the paper is concentrated on an online production of Henry V in 2020. The project is based on a new Polish translation by Piotr Kamiński and produced by Dariusz Rosiak, a journalist, as one of his regular Reports on the Condition of the World published on YouTube. Realised as a reading performance by three actors in front of an empty row of chairs, the production brings an innovative and revealing interpretation of the play, breaking new ground in the Polish reception of Shakespeare’s histories. The paper offers a brief review of the presence of history plays in Polish reception and introductory information on Rosiak’s YouTube channel and Kamiński’s translation as a background to a critical analysis of the production and its relevance to the here and now of our world.